Treatment of Retinitis Pigmentosa-Associated Cystoid Macular Oedema Using Intravitreal Aflibercept (Eylea) despite Minimal Response to Ranibizumab (Lucentis): A Case Report - Stacey A. Strong; Avinash Gurbaxani; Michel Michaelides (Case Reports in Ophthalmology, 2016)
Background: We present an interesting case of bilateral retinitis pigmentosa (RP)-associated cystoid macular oedema that responded on two separate occasions to intravitreal injections of aflibercept, despite previously demonstrating only minimal response to intravitreal ranibizumab. This unique case would support a trial of intravitreal aflibercept for the treatment of RP-associated cystoid macular oedema. Case Presentation: A 38-year-old man from Dubai, United Arab Emirates, presented to the UK with a 3-year history of bilateral RP-associated cystoid macular oedema. Previous treatment with topical dorzolamide, oral acetazolamide, and intravitreal ranibizumab had demonstrated only minimal reduction of cystoid macular oedema. Following re-confirmation of the diagnosis by clinical examination and optical coherence tomography imaging, bilateral loading doses of intravitreal aflibercept were given. Central macular thickness reduced and the patient returned to Dubai. After 6 months, the patient was treated with intravitreal ranibizumab due to re-accumulation of fluid and the unavailability of aflibercept in Dubai. Only minimal reduction of central macular thickness was observed. Once available in Dubai, intravitreal aflibercept was administered bilaterally with further reduction of central macular thickness observed. Visual acuity remained stable throughout. Conclusions: This is the first case report to demonstrate a reduction of RP-associated CMO following intravitreal aflibercept, despite inadequate response to ranibizumab on two separate occasions. Aflibercept may provide superior action to other anti-VEGF medications due to its intermediate size (115 kDa) and higher binding affinity. This is worthy of further investigation in a large prospective cohort over an extended time to determine the safety and efficacy of intravitreal aflibercept for use in this condition.